Control - Luqing Ye (IEEE Transactions on power systems)
Reliability analysis for hydro power stations for (N+M) and 2N fault tolerant modes (FTM) and their comparison from the standpoint of control and maintenance have been carried out in this paper. It shows that the (N+M) FTM is superior to 2N FTM in reliability and economics in most cases. So, (N+M) FTM is recommended for large power stations, especially for multi-unit plants. A simple method to choose the number of standby controllers is developed by optimizing the (N+M) FTM. The ideas and results proposed in this paper can be used not only for governing systems in hydro power stations but also for other industrial systems